Triploida em tilápia do Nilo: status hematológico, desempenho zootécnico e instabilidade genômica - Williane Ferreira Menezes (2023)
Triploidy is a chromosomal manipulation used with the aim of sterilizing individuals and controlling precocious sexual maturity and unwanted reproduction in a production system of some aquaculture species. Thus, the objective of this work was to evaluate the ploid condition of triploid Nile tilapia over time and better characterize them in terms of liver histology and blood and growth variables. The experiment was conducted at the Aquaculture Laboratory of the Veterinary School of the Federal University of Minas Gerais, Brazil, with approval from the ethics committee on the use of animals under protocol CEUA: 215/2021 (CEUA-UFMG). Eggs from female tilapia were fertilized, half of the spawning was subjected to a four-minute shock in water at 41°C at four minutes post-fertilization. Treated and control eggs were incubated and cultured for growth. Ploidy determination was performed by flow cytometry at two times. Initially to separate the control, treated (but not triploid) and triploid groups. And later, in the same adult animals. The animals were periodically weighed for growth control, and at the end of the experiment, blood samples were collected for hematological analysis and then, the animals were euthanized, to collect the liver for morphological analysis. With the results of the first cytometry, 14 triploid animals were observed, while the ploidy analysis of the adult animals indicated that only 12.5% of the live triploid individuals remained triploid and the others lost sets of chromosomes. The growth performance of triploid tilapia was superior to that of diploid tilapia during the juvenile stage, but similar in adults. Among the hematological parameters, the highlight is that triploidy led to an increase in the size of erythrocytes as expected due to the presence of an extra set of chromosomes. Liver histology was analyzed and indicated that tilapia that have lost a set of chromosomes did not show significant histopathological changes. It is important to reassess the feasibility of using triploids as an option for Nile tilapia production or even as a research model. Our results suggest that due to chromossomal instabilities caused by polyploidization, the generation of a triploid tilapia stock may have low efficiency.